Effect of Humidity on the Energy and CO2 Separation Characteristics of Membranes in Direct Air Capture Technology - Kamil Niesporek; Grzegorz Wiciak; Janusz Kotowicz; Oliwia Baszczeńska (Energies)
Membrane-based direct air capture of CO2 (m-DAC) is a promising solution for atmospheric decarbonization. Despite growing interest, the impact of relative air humidity on the performance of m-DAC systems is often neglected in the literature. This study presents detailed parametric analyses that take into account humidity variability and several hypothetical scenarios regarding membrane selectivity toward water vapor. Specifically, cases were considered where the permeance of H2O relative to CO2 was assumed to be 0.5, 2, and 5 times higher, which allowed for a systematic assessment of the impact of relative humidity on process performance. The calculations were carried out both for membranes with assumed separation parameters and for the PolyActiveTM membrane, enabling a realistic evaluation of the influence of atmospheric conditions on the process. The results show that an increase in humidity in the analyzed range from 0 to 80% can lead to a rise in the energy intensity of the process by up to approximately 34%, and an increase in total power demand by around 29%. As humidity increases, key process parameters such as CO2 purity in the permeate and recovery rate decrease. The water vapor content in the permeate in a single-stage membrane separation process can reach up to 60%. It is recommended to use gas drying systems and to develop membranes with low H2O permeance in order to reduce the energy cost of the process. The potential location of m-DAC systems should preferably be in regions with low air humidity. The study highlights the necessity of considering local climate conditions and the need for further research on membrane selectivity.